(3GdLfi GdOGfj aj MQha GdeYGfjs - (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, HOQ GdOjf CHh eMeO, GHf Ge bGSe , J (B749 (3g` s
(3ChdgG (B:s
(3hHYO, aEfg deG cGfJ ebGUO cdGe GdYQH Ydi GNJdGa Ufhag eHfjkG CcKQgG Ydi eYGfj MQhag s
(3BNQgG (B:s
(3hEfeG CgedJ PcQgG gfGc dTgQJgG hZQGHI Gdbhd HMQajJgG hGdcdGe YdjgG ehVY gh Cdjb Hg ef gPG GdcJGH, hGddg Gdehab, ced cJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3fSNI QGHYI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3hHBNQgG eWGdYI JeJ SfI (B964(3g``s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs